Book review: Method and theory in cross-cultural psychological assessment by Alexis Retief - Bentley, Alastair M. (PINS-Psychology in Society, 2025)
One of the principal reasons for writing a book must be that the writer has something new to say or alternatively can say what has already been said in a better or more lucid way. In neither case do these apply to Retiefs foray into the area of cross-cultural methodology. Several issues make this a disappointing book.